2012
DOI: 10.2111/rem-d-11-00042.1
|View full text |Cite
|
Sign up to set email alerts
|

Grazing Distribution and Diet Quality of Angus, Brangus, and Brahman Cows in the Chihuahuan Desert

Abstract: Grazing distribution can be improved by using adapted cattle breeds that travel to distant areas of extensive pastures. A 2-yr study was conducted to evaluate grazing distribution and diet quality of Angus, Brangus, and Brahman cows (seven cows per breed group) in the Chihuahuan Desert during three seasons (winter, early summer, and late summer) using three pastures. Two GPS collars were randomly assigned to each breed group and cow positions were logged every 10 min for 10-to 14-d periods in each pasture (3 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…These differences between biotypes has also been observed between Zebu cattle ( Bos indicus , Brahman breed) and a British breed (Angus) in desert areas [ 95 ]. Brahman cows travel longer daily distances than Angus cows and Brangus (Brahman × Angus) with no differences in average distance to water, whereas Angus cows maintain a more linear grazing route than Brangus or Brahman cows.…”
Section: Effect Of Animal Factors and Social Interactions On Site Use Preferencementioning
confidence: 74%
“…These differences between biotypes has also been observed between Zebu cattle ( Bos indicus , Brahman breed) and a British breed (Angus) in desert areas [ 95 ]. Brahman cows travel longer daily distances than Angus cows and Brangus (Brahman × Angus) with no differences in average distance to water, whereas Angus cows maintain a more linear grazing route than Brangus or Brahman cows.…”
Section: Effect Of Animal Factors and Social Interactions On Site Use Preferencementioning
confidence: 74%
“…In addition, our results indicate that the area explored by grazing livestock might also be influenced by forage quality attributes that are not captured with MODIS NDVI. Increased NDVI in this study is possibly linked with higher nitrogen content and digestibility of the forage species [43][44][45] , which is likely to have reduced the need for animals to search large areas of a pasture to meet their nutritional requirements. Accordingly, cows in this study showed more concentrated search patterns and spent more time grazing during weeks when pasture NDVI was high (i.e., during peak green seasonal stage).…”
Section: Livestock Movement Patternsmentioning
confidence: 89%
“…Cattle were considered not active if the distance traveled between two successive GPS locations was less than 20 m and the left-right and fore-aft sensor counts were less than 50. These values were based on research conducted at the CDRRC which found a 90% accuracy in predicting non-active and active behavior (Russell et al, 2012).…”
Section: Gps Collar Tracking Datamentioning
confidence: 99%